Solitary Peutz-Jeghers type harmartomatous polyp in duodenum with gastric foveolar epithelium: a case report - Eugene Choi; Junghwan Lee; Youngsoo Park (Korean Society of Pathologists & the Korean Society for Cytopathology, 2023)
Peutz-Jeghers type hamartomatous polyp is known to be associated with Peutz-Jeghers syndrome, which shows characteristic multiple hamartomatous polyp involvement in the gastrointestinal tract, combined with mucocutaneous symptom, familial history of Peutz-Jeghers syndrome or STK11/LTB1 mutation. However, some cases showing histologic appearance of the polyps discovered in Peutz-Jeghers syndrome while lacking other diagnostic criteria of the syndrome have been reported, and these are called solitary Peutz-Jeghers type polyps. Herein, we report a case of solitary Peutz-Jeghers type polyp covered with heterotopic epithelium. The patient was 47-year-old female without any mucocutaneous symptoms nor familial history of Peutz-Jeghers syndrome. Microscopic examination revealed Peutz-Jeghers type hamartomatous polyp in duodenum covered with gastric type foveolar epithelium. Considering the definition of hamartomatous polyp, which is, the abnormal overgrowth of the indigenous epithelial component, the histological feature of current case is noteworthy in a point that it shows proliferation of heterotopic component, rather than the indigenous component.